Cardiovascular risk profile with SCORE2 and SCORE2-OP: comparing Portugal, Spain, Italy, and France using the new European predictive models - Fontainhas, Mariana; Gavina, Cristina; Miranda, Joana; Pereira-Silva, Raquel; Guichard, João; Seixas, Daniela; Araújo, Francisco (Frontiers in Cardiovascular Medicine, 2024)
IntroductionThis study aims to characterize the cardiovascular risk profile in countries with low-to-moderate cardiovascular mortality risk (Italy, Portugal, France, and Spain) using the SCORE2 and SCORE2-OP models. It also examines regional variations and the involvement of healthcare professionals in performing risk assessments.MethodsA retrospective observational study was conducted using data from 24,434 cardiovascular risk assessments performed between December 2022 and July 2023 through a digital application used by physicians. The assessments used the SCORE2 model for individuals aged 40–69 and the SCORE2-OP model for those aged 70 and older. Risk stratification into “low-to-moderate,” “high,” and “very high” categories was analyzed based on individual risk factors such as age, smoking habits, systolic blood pressure, and cholesterol levels.ResultsApproximately 50%–60% of individuals in these countries were classified as having “high” or “very high” cardiovascular risk. The highest proportions were observed in Portugal (62.44%) and Italy (64.05%), while lower proportions were found in Spain (46.65%) and France (52.74%). Regional analysis identified areas with the highest cardiovascular risk, such as Portalegre in Portugal and Apulia in Italy. Key risk factors included older age, smoking, high systolic blood pressure, and high non-HDL cholesterol. General practitioners were the primary healthcare professionals conducting these assessments.DiscussionThe study highlights a significant proportion of individuals with “high” or “very high” cardiovascular risk in countries with low-to-moderate mortality risk. These findings underscore the need for targeted cardiovascular disease prevention strategies and the crucial role of general practitioners in managing cardiovascular risk.